5ʹUTR polymorphism in the serotonergic receptor HTR3A gene is differently associated with striatal Dopamine D2/D3 receptor availability in the right putamen in Fibromyalgia patients and healthy controls—Preliminary evidence. Issue 5 (7th January 2020) - Ledermann, Katharina; Hasler, Gregor; Jenewein, Josef; Sprott, Haiko; Schnyder, Ulrich; Martin‐Soelch, Chantal
Abstract: Background: Extensive literature has investigated the role of serotonin (5‐HT) in the control of the central dopamine (DA) systems, and their dysfunction in the pathological conditions. 5‐HT stimulates the local DA release in striatal regions via activation of various receptors including serotonin receptor‐3 (5‐HT3). Several studies have related polymorphisms (SNPs) in the serotonin receptor‐3 (HTR3) genes to be associated with the pain modulation and endogenous pain suppression. A few studies suggested a functional role of 5ʹUTR SNP in the serotonergic receptor HTR3A gene (rs1062613) in the development of the chronic pain and Fibromyalgia syndrome (FMS) in particular. Here, we investigated the effect of a 5ʹUTR SNP in the serotonergic receptor HTR3A gene (rs1062613) on striatal dopamine D2/D3 receptor (DRD2) availability and reward‐associated DA release in response to unpredictable monetary rewards in 23 women with FMS and 17 age‐matched healthy female controls. Furthermore, we aimed to examine if SNP rs1062613 is associated with thermal pain and pain tolerance thresholds. Methods: We used PET and [ 11 C]raclopride to assess the DRD2 availability. In the same participants we used the [ 11 C]raclopride PET bolus‐plus‐infusion method to measure the [ 11 C]raclopride receptor binding potential (ΔBP) between an unpredictable reward condition and a sensorimotor control condition. DRD2 availability and ΔBP were assessed in MRI‐based striatal regions of interest. Thermal pain and pain tolerance thresholds were assessed outside the scanner. Results: The frequency of SNP rs1062613 genotype differed significantly between groups, indicating that CC homozygotes were more frequent in FMS patients (82.6%) than in healthy controls (41.3%). Our results showed a significant main effect of SNP rs1062613 on [ 11 C]raclopride binding potential in the right caudate nucleus indicating a higher DRD2 receptor availability for CC‐genotype of this SNP. Furthermore, we found a significant group × SNP interaction on [ 11 C]raclopride binding potential in the right putamen, indicating a higher DRD2 availability in T‐carriers compared to CC genotype of SNP rs1062613 in FMS patients, whereas this effect was not present in healthy controls. However, we did not find an influence of SNP rs1062613 on reward‐related DA release. In addition, there was no association between SNP rs1062613 and pain threshold or pain tolerance threshold in our data. Conclusion: These preliminary results indicate that SNP rs1062613 in the serotonergic receptor HTR3A gene possibly modulates the DRD2 receptor availability. Abstract :